Depression experiences and coping strategies of UPV Social Science students - Abello, Merwin M .; Jison, Anne Therese G. (2005.)
Depression affects all kinds of people: young and old, rich to poor, famous to unknown. On students depression has been linked to poor school performance , absenteeism, alcohol and drug abuse, running away, and feelings of worthlessness and hopelessness., The study aims to find out the students' personal experiences on depression and the coping strategies they employ for their depressedmood. It seeks to accomplish the following objectives: (1) To know the causes of depression as reported by male and female students; (2)To find out the effects of depression on male and female students; (3)To determine whether male and female students experience depression in different ways; and (4) To ascertain whether male and female college students who experienced depression differ in their coping strategies. The respondents of the study are students of the Division of Social Sciences, College of Arts and Sciences of the University of the Philippines in the Visayas. The survey method was used in gathering data. The respondents were selected using simple random sampling method. From the total population of the Division of Social Sciences, a sample size of sixty-two (62) was drawn using the fish bowl method. Then a self-administered quationnaire was distributed among them. The study shows that the common causes of depression among students are greater academic demands, problems in the family and intimate relationship. Among male and female students depression usually interferes with their academic and social functioning. The study also shows that male and female respondents have similar depression experiences. In coping with their depression, the respondents consider the problem-focused coping strategy. Majority of the respondents come up with the strategies and activities that can help them in their depression. Both sexes in the study rely on the social support; but it was found out that females seek more social support than males do. The researchers recommend conducting the study using bigger sample as well as using a certain scale that would determine or measure the level of depression and the coping strategies of the respondents.
Thesis (Undergraduate, Bachelor of Arts in Sociology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Depression (Behavior); UPV Social Sciences Students -- Depression experiences; UPV Social Sciences Students -- Coping strategies